A Multicomponent Measure of Writing Motivation With Basic College Writers - MacArthur, Charles A.; Philippakos, Zoi A.; Graham, Steve (Learning disability quarterly, 2016)
The purpose of the current study was to develop and validate a measure of motivation for use with basic college writers that would measure self-efficacy, achievement goals, beliefs, and affect. As part of a design research project on curriculum for community college developmental writing classes, 133 students in 11 classes completed the motivation scales at the beginning and end of the semester along with measures of writing quality. Single factors were found for self-efficacy and affect. For goal orientation, factors were found for mastery, performance, and avoidance goals. For beliefs, factors were found for beliefs related to the content of writing and to conventions. Anticipated patterns of correlations among the factors were found. The validity of the scales was further supported by significant differences in the anticipated direction between higher and lower level classes on five of seven factors. In addition, significant changes were noted from pretest to posttest in the anticipated direction on six of seven factors.